КЛАСТЕР УСУЛИНИ “ГЕТЕРОЦИКЛИК БИРИКМАЛАР - МЕТАБОЛИТ ВА ДОРИВОР МОДДАЛАР СИФАТИДА” МАВЗУСИДА ҚЎЛЛАШ - Сафарова, Н.С. (SCIENCE and SOCIETY, 2021)
This article describes the principles of application of the cluster method in the course of the topic "Heterocyclic compounds" of medical chemistry for first-year medical students. It also reveals the peculiarities of the application of the cluster method during lectures, practical classes and self-study, and offers specific practical recommendations.